Discovery and Evolution of a Divergent Coronavirus in the Plateau Pika From China That Extends the Host Range of Alphacoronaviruses - Zhu, Wentao; Yang, Jing; Lu, Shan; Jin, Dong; Wu, Shusheng; Pu, Ji; Luo, Xue-lian; Liu, Liyun; Li, Zhenjun; Xu, Jianguo (Frontiers in Microbiology, 2021)
Although plateau pikas are the keystone species in the plateau ecosystem of the Qinghai Province of China, little is known about their role in the evolution and transmission of viral pathogens, especially coronaviruses. Here, we describe the characterization and evolution of a novel alphacoronavirus, termed plateau pika coronavirus (PPCoV) P83, which has a prevalence of 4.5% in plateau pika fecal samples. In addition to classical gene order, the complete viral genome contains a unique nonstructural protein (NS2), several variable transcription regulatory sequences and a highly divergent spike protein. Phylogenetic analysis indicates that the newly discovered PPCoV falls into the genus Alphacoronavirus and is most closely related to rodent alphacoronaviruses. The co-speciation analysis shows that the phylogenetic trees of the alphacoronaviruses and their hosts are not always matched, suggesting inter-species transmission is common in alphacoronaviruses. And, PPCoV origin was estimated by molecular clock based on membrane and RNA-dependent RNA polymerase encoding genes, respectively, which revealed an apparent discrepancy with that of co-speciation analysis. PPCoV was detected mainly in intestinal samples, indicating a potential enteric tropism for the virus. Overall, this study extends the host range of alphacoronaviruses to a new order (Lagomorpha), indicating that plateau pikas may be the natural reservoir of PPCoV and play an important and long-term role in alphacoronavirus evolution.